Erratum: Management of cardiovascular disease patients with confirmed or suspected covid-19 in limited resource settings (Global Heart (2020) 15:1 (44) DOI: 10.5334/gh.823) - Prabhakaran, D. (Ubiquity Press, 2021)
10.5334/GH.885